The relationship between househods with proper sanitation and stunting prevalence: A case study - Ramadhani Jaka Samudra (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Stunting reflects a failure in the optimal growth and development of children and is influenced by a range of factors. The World Health Organization (WHO) sets the global stunting prevalence target at below 20%. In response, the Indonesian government has set a national target of reducing stunting to 14% by the year 2024. While direct causes of stunting include inadequate breastfeeding and poor nutritional intake, indirect factors such as access to safe and proper sanitation at home also play a significant role in stunting prevalence. Purpose: To analyze the relationship between access to proper sanitation facilities in households and the prevalence of stunting. Method: This research utilizes secondary data from the Indonesian Central Bureau of Statistics (BPS) on household sanitation coverage in 2022, along with data on stunting prevalence from the 2022 Indonesian Nutrition Status Survey. The data were analyzed using a bivariate correlation test via SPSS software to determine the strength and direction of the relationship between the two variables. Results: The analysis produced a p-value of 0.00, which is below the significance level (α = 0.05), indicating a statistically significant correlation. The Pearson correlation coefficient was found to be -0.589, suggesting a moderate negative relationship between proper household sanitation and stunting prevalence. This means that as the number of households with proper sanitation increases, the rate of stunting decreases and conversely, lower sanitation access is associated with higher stunting levels. Conclusion: The study concludes that proper sanitation in households has a moderate inverse relationship with the prevalence of stunting in Indonesia.